EVALUASI TOLERANSI TANAMAN KEDELAI (Glycine max (L.) Merrill) REGENERAN M4 HASIL RADIASI SINAR GAMMA TERHADAP SALINITAS - Junita Junita Gurning; Emmy Harso Kardhinata; Eva Sartini Bayu (Universitas Sumatera Utara, 2013)
High content of NaCl in soil inhibits plant growth and production. Mutation is a technique increase genetic variability in plant, so that getting of tolerance plant to NaCl. The objective of this research was to know response M4 soybeans generation respon result of gamma ray to get tolerance soy to NaCl. The research was conducted at Tanjung Selamat land, Deli Serdang district, in April – June 2012 using factorial randomized block design with 2 factors as population M4 Soybeans generation (0, 10, 20, 30 krad per plant) and NaCl concentration (0, 1500, 3000, 4500 ppm). Parameters measured were plant germination, viability, high of plant, nodes per plant, number of branch at especial bar, root height, weight of dry root, weight of dry leaves, number of pods per plant, number of empty pods per plant and weight of 100 seeds. The results showed dosage of gamma ray on M4 Soybeans generation was affect significantly to plant germination, viability, and high of plant. NaCl concentration affect significantly to viability, and high of plant. The interaction between population M4 Soybeans generation and NaCl concentration affect significantly to plant germination (3,67 days), viability (100%), and high of plant (16.38 cm). Keywords : M4 soybeans, NaCl, gamma radiation